Rethinking Marriage, Rejecting Parenthood: Childfree Intent in the Fatwas of Syaikh Syauqi Ibrahim ‘Allam and Syaikh Ahmad Al-Raisuni - Muhammad Zainuddin; Zulpahmi Lubis (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2026)
The rise of the childfree phenomenon in the modern era has triggered an epistemological clash in contemporary Islamic law, specifically between fulfilling individual reproductive autonomy rights and the collective obligation to maintain the existence of the Muslim population. This polarization creates a strong academic urgency to be investigated due to the legal uncertainty arising from differing istinbāṭ (legal derivation) methods among global fatwa authorities in responding to this social shift. This normative legal research (library research) aims to analyze and compare the views and legal derivation methods of Syaikh Syauqi Ibrahim Allam and Syaikh Ahmad al-Raisuni regarding marrying with the intention of being childfree. A conceptual and comparative approach was utilized, with qualitative data analysis conducted through descriptive-comparative methods. The results show that Syaikh Syauqi Ibrahim Allam tends to permit childfree under certain conditions based on the principle of al-aṣlu fi al-ashyā’ al-ibāhah (the presumption of permissibility) and mutual consent for the sake of welfare (maṣlaḥah). Conversely, Syaikh Ahmad al-Raisuni disallows permanent childfree choices because they contradict ḥifẓ al-nasl (preservation of progeny) as a primary objective of Sharia, employing fiqh al-maqāṣid (objectives-based jurisprudence), sadd al- żari'ah (blocking the means), and fiqh al-māl (jurisprudence of outcomes) to protect the collective interest. This study concludes that the legal divergence between the two scholars is heavily influenced by their methodological approaches in prioritizing different levels of welfare within Sharia objectives (maqāṣid al-syarīʿah). The implications of this research offer a theoretical contribution to the reconstruction of contemporary Islamic legal methodology, encouraging a more adaptive use of consequential analysis (fiqh al-māl) when addressing modern family issues. This study suggests that Islamic fatwa institutions and family counselors implement balanced and case-by-case legal approaches, while recommending that future researchers expand this study through empirical field research.